2010
DOI: 10.1177/0002764210381705
|View full text |Cite
|
Sign up to set email alerts
|

Cracked and Shattered Ceilings: Gender, Race, Religion, Age, and the Ideal Candidate

Abstract: Image as a transaction between what candidates say and do and the way voters compare that behavior with their personal vision of what candidates should be or do stimulates at least four critical questions important to political communication. First, what qualities or attributes do voters believe are important for a presidential candidate to possess-what are the dimensions of the "ideal" presidential candidate? Second, do these views change with time and with candidates, or are they fairly consistent across ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Table 2 presents the mean importance ratings for all candidate characteristics measured across all eight campaigns. As noted in Trent et al (1993, 1997, 2001, 2005, 2010, 2013), importance ratings do not swing markedly across campaigns. Those characteristics considered important (or unimportant) in 1988 were still considered important (or unimportant) in 2016.…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…Table 2 presents the mean importance ratings for all candidate characteristics measured across all eight campaigns. As noted in Trent et al (1993, 1997, 2001, 2005, 2010, 2013), importance ratings do not swing markedly across campaigns. Those characteristics considered important (or unimportant) in 1988 were still considered important (or unimportant) in 2016.…”
Section: Resultsmentioning
confidence: 59%
“…This study was designed to extend surveys of voters taken during the 1988, 1992, 1996, 2000, 2004, 2008, and 2012 New Hampshire primaries into 2016. In accordance with the earlier works, the purpose of the 2016 study was to determine those attributes voters considered most important for presidential hopefuls to possess and compare them with earlier New Hampshire primary campaigns (Trent, Mongeau, Trent, Kendall, & Cushing, 1993; Trent, Short-Thompson, Mongeau, & Metzler, 2013; Trent, Short-Thompson, Mongeau, Nusz, & Trent, 2001; Trent, Short-Thompson, Mongeau, Metzler, Erickson, & Trent, 2010; Trent, Short-Thompson, Mongeau, Metzler, & Trent, 2005; Trent, Trent, Mongeau, & Short-Thompson, 1997). Thus, the first research question, did voters’ images about what was important and what was unimportant about candidate attributes change?…”
Section: Focus Of the Studymentioning
confidence: 94%
See 1 more Smart Citation
“…Some factors have been found to be important across elections and candidates, and the influence of others has varied based on electoral context. Trent et al (2010) examined trait importance over six presidential elections and found honesty to be the most important in four elections and second most important in two. Winfrey (2018) examined presidential elections from 2000 to 2012 and found leadership, caring, morality, and intelligence were important factors in support of presidential candidates, but the importance of each trait varied based on electoral context.…”
Section: Candidate Image and The Presidencymentioning
confidence: 99%
“…This literature has focussed predominantly on the United States and on a relatively small number of characteristics, most obviously candidate sex and race/ethnicity. But more recent research has begun to extend the study further, both geographically and in terms of subject area, finding other significant characteristics, including visual image (Banducci et al, 2008, Mattes and Milazzo, 2014), occupation and wealth (Campbell and Cowley, 2014a, McDermott, 2005), age (Campbell and Cowley 2014b, Trent et al, 2010) and residency (Arzheimer and Evans, 2012, 2014).…”
mentioning
confidence: 99%